Stachytarpheta sobraliana (Verbenaceae), a new species from the Serra de São José, Minas Gerais, Brazil - Cardoso, Pedro Henrique; Alves, Ruy José Válka; Neto, Luiz Menini; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2019)
We describe a new species of Stachytarpheta endemic to the campos rupestres of the São José mountain range in south-central Minas Gerais, Brazil. Stachytarpheta sobraliana is characterized by canescent branches, abaxial leaf surfaces, bracts and calyces; leaves congested at the stem apices of adult individuals; ovate to orbicular leaf blades with rounded apices and rounded to obtuse bases; bracts with caudate, subulate apices; four-toothed calyces; and corollas with cobalt blue to purple tubes and sky blue to lilac laciniae. We provide a detailed diagnosis, a comparison with the morphologically most similar and sympatric species, a key to the informal group “commutata”, conservation status and photos of live specimens.